Assessing potential for aortoiliac vascular injury from venoarterial extracorporeal membrane oxygenation cannulae: An in vitro particle image velocimetry study. Issue 2 (15th October 2020) - Haymet, Andrew B.; Boone, Alice; Vallely, Michael P.; Malfertheiner, Maximilian Valentin; Pauls, Jo P.; Suen, Jacky Y.; Fraser, John F.
Abstract: Limb ischemia is a major complication associated with peripheral venoarterial extracorporeal membrane oxygenation (VA‐ECMO). The high velocity jet from arterial cannulae can cause "sandblasting" injuries to the arterial endothelium, with the potential risk of distal embolization and end organ damage. The aim of this study was to identify, for a range of clinically relevant VA‐ECMO cannulae and flow rates, any regions of peak flow velocity on the aortic wall which may predispose to vascular injury, and any regions of low‐velocity flow which may predispose to thrombus formation. A silicone model of the aortic and iliac vessels was sourced and the right external iliac artery was cannulated. Cannulae ranged from 15 to 21 Fr in size. Simulated steady state ECMO flow rates were instituted using a magnetically levitated pump (CentriMag pump). Adaptive particle image velocimetry was performed for each cannula at 3, 3.5, 4, and 4.5 L/min. For all cannulae, in both horizontal and vertical side hole orientations, the peak velocity on the aortic wall ranged from 0.3 to 0.45 m/s, and the regions of lowest velocity flow were 0.05 m/s. The magnitude of peak velocity flow on the aortic wall was not different between a single pair versus multiple pairs of side holes. Maximum velocity flow on the aortic wall occurred earlier at a lower pump flow rate in the vertical orientation of distal side holes compared to a horizontal position. The presence of multiple paired side holes was associated with fewer low‐velocity flow regions, and some retrograde flow, in the distal abdominal aorta compared to cannulae with a single pair of side holes. From this in vitro visualization study, the selection of a cannula design with multiple versus single pairs of side holes did not change the magnitude of peak velocity flow delivered to the vessel wall. Cannulae with multiple side holes were associated with fewer regions of low‐velocity flow in the distal abdominal aorta. Further in vivo studies, and ideally clinical data would be required to assess any correlation of peak velocity flows with incidence of vascular injury, and any low‐velocity flow regions with incidence of thrombosis.